Pelatihan Pembuatan Sala Lauak dalam Rangka Peningkatan Potensi Ekonomi dan Usaha Mikro Kecil (UMK) di Desa Bandar Padang, Kabupaten Indragiri Hulu - Sakur, Sakur; Rosyidah, Aliya Shabrina; Putri, Cindy Aulia; Yuli, Dea Fitri Risya; Ramadhani, Intan; Aulia, Messo; Firnanda, Nia; Ananta, Putri Dwi; Dewi, Sukma; Febriani, Viola (Journal of Community Sustainability, 2024)
Village potential is the main capital in developing the economy, so empowerment of village potential needs to be done to welcome the nation's progress. The development of economic potential in Bandar Padang Village is something that needs to be considered by observing the existing potential. This observation eventually made the Sala Lauak Making Training an activity carried out in order to achieve this goal. Sala lauk is one of the typical Minangkabau snacks, West Sumatra, where the main ingredients are dried fish and rice flour. This snack has a unique taste and is loved by many people. By looking at the potential of Bandar Padang village during the dry season, where villagers are looking for fish in the rivers and processed into dried fish, the 2024 Riau University MBKM Kukerta Students are trying to introduce one of the typical Minangkabau snacks. Students of Kukerta MBKM Riau University 2024 held training activities for making Sala Lauak, with the hope of maximizing the empowerment of the village's potential and can increase the village's Micro and Small Enterprises (MSEs) by highlighting the village's own products and can preserve Indonesia's culinary heritage. In this training, participants were guided in making the Sala Lauak such as ingredients used in the manufacturing process and proper cooking techniques in order to improve the taste of the sala side dish. This activity involved Bandar Padang villagers, especially teenagers and adults.